2019
DOI: 10.1002/app.47944
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication behaviors of PVA‐casted LSPEEK hydrogels in artificial cartilage repair

Abstract: Poly(ether-ether-ketone) (PEEK) is a known bio-implant material due to its excellent mechanical properties. However, the challenging issue of high friction coefficient limits the PEEK applications. In this article, double-layered hydrogel material was obtained by laser processing, surface sulfonation, and poly(vinyl alcohol) (PVA) casting. Characterizations of FT-IR, XRD, SEM, and 3Dmorphology demonstrate that PVA-LSPEEK hydrogel was achieved successfully. PVA-LSPEEK exhibits an extremely smooth surface with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…[ 34,35 ] Cast drying is another physical crosslinking technique that is occasionally applied combined with the freeze‐thaw method. [ 54,61,62 ] The sample is held at a certain temperature and humidity (natural air drying, hot air drying, or freeze‐drying [ 63 ] ) for a couple of days to one week until the evaporation is completed. Besides, theta gelation is also a physical crosslinking process that is not so often used.…”
Section: Physicochemical Properties Of Pva and Hydrogel Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 34,35 ] Cast drying is another physical crosslinking technique that is occasionally applied combined with the freeze‐thaw method. [ 54,61,62 ] The sample is held at a certain temperature and humidity (natural air drying, hot air drying, or freeze‐drying [ 63 ] ) for a couple of days to one week until the evaporation is completed. Besides, theta gelation is also a physical crosslinking process that is not so often used.…”
Section: Physicochemical Properties Of Pva and Hydrogel Preparationmentioning
confidence: 99%
“…Zhou et al. [ 61 ] cast PVA hydrogel onto a polyether ether ketone (PEEK) base prepared by laser processing and surface sulfonation to obtain a “soft‐hard” structure (PVA‐LSPEEK); Zhao et al. [ 97 ] also used a similar “PVA‐on‐toughened‐base” structure, where PVA hydrogel is combined with a 3D‐printed titanium scaffold; Jiang et al.…”
Section: Functional Modifications Of Pva Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 By combining PVA and PEEK through laser processing and surface-sulfonation methods, Zhou prepared a bilayer hydrogel that not only exhibits excellent mechanical adhesion to PEEK substrates but also has good water lubrication properties under high loads. 33 Polyethylene glycol (PEG) as a common polymer water-soluble lubricating material; in solution, the PEG molecular chain is easily stretched to form a hydrogenbond-rich network. Animal experiments have demonstrated that PEG has low toxicity and good biocompatibility, so that it is suitable for use in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The great vibrations absorb properties combined with highly wear resistance make the polymeric materials gradually replace the traditional water‐lubricated bearing materials 6–8 . Polyetheretherketone (PEEK) is a kind of liner chain plastics with great mechanical properties, great heat stability, and high chemical resistance 9–11 . PEEK only contains of ether linkage and ketone, neither of which can react with water or metals under the working conditions of water‐lubricated bearings.…”
Section: Introductionmentioning
confidence: 99%